Xerophthalmia: Risk Factors and Prevention - Almaina Puteri Jasmine Almaina; Mafalda Marzon; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Xerophthalmia refers to a range of ocular symptoms caused by vitamin A deficiency, ranging from night blindness and Bitot’s spots to corneal xerosis, ulceration, and keratomalacia, which can lead to blindness. Globally, the incidence of xerophthalmia has been estimated at 350.000 cases annually. The majority of children who have vitamin A deficiency severe enough to cause bilateral corneal melting, perforation and blindness associated with xerophthalmia die within the first year of becoming blind. It has an essential role in maintenance of corneal and conjunctival epithelization, as well as photoreceptor transduction in the retina. On the eye, vitamin A deficiency results in night blindness, xerosis of the conjunctiva and cornea, and ultimately corneal ulceration and necrosis of the cornea. Several risk factors for vitamin A deficiency and xerophthalmia have been established through epidemiological studies, including demographic, geographic, childhood, parental and household factors. Prevention of xerophthalmia can be done with three strategies, such as periodic high-potency vitamin A supplementation, food fortification, and improving availability of foods containing vitamin A.